2016
DOI: 10.1016/j.icarus.2016.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric aftermath of the 2010 Storm on Saturn as observed by the TEXES instrument. I. Temperature structure

Abstract: We report on spectroscopic observations of Saturn's stratosphere in July Icarus 221, 560-586). Our observations confirm that the beacon B0 vertical structure determined by CIRS, with a maximum temperature of 180 ± 1K at 2 hPa, is overlain by a temperature decrease up to the 0.2-hPa pressure level.Our retrieved maximum temperature of 180 ± 1K is colder than that derived by CIRS (200 ± 1K), a difference that may be quantitatively explained by terrestrial atmospheric smearing. We propose a scenario for the format… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
(109 reference statements)
2
16
0
Order By: Relevance
“…We believe this issue is a systematic one and therefore should not affect relative latitudinal and longitudinal variations. Fouchet et al (2016) found similar offsets in comparing temperatures derived from Cassini-CIRS and IRTF-TEXES measurements of Saturn, which they attributed to terrestrial atmospheric smearing of the beam measured by the telescope. We suggest that a similar issue is present in the TEXES observations presented in this work.…”
Section: Radiance Differencessupporting
confidence: 55%
“…We believe this issue is a systematic one and therefore should not affect relative latitudinal and longitudinal variations. Fouchet et al (2016) found similar offsets in comparing temperatures derived from Cassini-CIRS and IRTF-TEXES measurements of Saturn, which they attributed to terrestrial atmospheric smearing of the beam measured by the telescope. We suggest that a similar issue is present in the TEXES observations presented in this work.…”
Section: Radiance Differencessupporting
confidence: 55%
“…Sudden stratospheric warming on Earth's high and mid-latitude regions are associated with downward wind propagation anomalies of the Quasi-Biennial Oscillation (Lu et al, 2008). Is it possible that the extremely warm stratospheric disturbance in the aftermath of the Great White Storm of 2010-2011 (Fletcher et al, 2011(Fletcher et al, , 2012Fouchet et al, 2016) is due to a disruption of the downward propagation of the equatorial oscillation on Saturn? Conversely, Cassini observations showed that the occurrence of this huge storm disturbed the equatorial oscillations (Fletcher et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In essence, α represents the relative weights to give to the measurements and to the a priori at each step of the iteration process. Following Fouchet et al (2016), we found that an optimum choice of α (in terms of stability and rapidity of the algorithm) was achieved by equalling the traces of the αKSK T and E matrices. Iterations were performed until convergence -defined by the constancy of the fit quality (rms between observations and models) within 1 % from an iteration to the next one -was reached.…”
Section: Methodsmentioning
confidence: 99%